TEACHING PRACTICUM ACTIVITIES AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES - VIETNAM NATIONAL UNIVERSITY, HANOI FROM THE TEACHERS’ AND STUDENTS’ PERSPECTIVES - Lan, Nguyen Thuy (VNU Journal of Foreign Studies, 2019)
Practicum is always an important and indispensable component in a training program in general and a foreign language teacher education program in particular. Through this activity, students will be able to put their acquired knowledge into practice, thereby shortening the gap of "apprenticeship" of young graduates. To assess the appropriateness of the current teaching practicum at the University of Languages and International Studies - Vietnam National University, Hanoi (ULIS-VNU), the study has conducted a survey with 30 teachers and 100 students. The initial results show that in terms of practicum duration and implementation time, most teachers required that the duration should be increased because 06 weeks was not enough for students to practice and learn from experience. However, most students believed that the current internship was reasonable in the final semester of the training program. Concerning the time of starting the internship, the majority of teachers said that students should start their internship in the last semester when they had sufficient foreign language skills and pedagogical skills; students conversely preferred to practice earlier. In terms of skills and knowledge that need to be equipped for students, all participants agreed that the training of soft skills should be added. In terms of the highschools that receive student teachers, most participants believed that those should be selected by the university; however, the schools’ level of support and effectiveness in guiding students were not highly appreciated. The initial findings of this study may serve as suggestions for the continous revision and improved facilitation of the teaching practicum activities at ULIS-VNU to achieve the goals of training prospective student-teachers.